Miles Morales. Vol. 6, All eyes on me - Ahmed, Saladin; Lord, Phil, 1977-; Miller, Chris, 1975-; Powers, Kemp; Ziglar, Cody (Marvel Worldwide, Inc., 2021)
"Happy tenth anniversary, Miles Morales! The young Spider-Man has run the gauntlet of his very own Clone Saga--but the shocking fallout will leave Miles and the people he loves permanently changed. You may think we're joking or blowing it out of proportion -- but we are not! Change is on the horizon -- and as a who's who of Miles Morales Spider-Creators web together a celebration of his first decade in comics, it's time to look ahead to his future! And although for Miles, the scars are fresh and his path is uncertain, the future has never looked brighter. Celebrate Miles' birthday in style, and join mighty Marvel for an anniversary celebration like no other!"--Amazon.